2015
DOI: 10.1080/10942912.2015.1071841
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal and High Electric Fields on Secondary Structure of Peanut Protein

Abstract: This study evaluated the effect of the thermal and high electric field stresses on the secondary structure conformation of peanut protein using Fourier transform infrared spectroscopy. The amide I region between the wavelengths 1700-1600 cm-1 of the spectra were studied for different thermal and high electric field treatments. Within thermal treatments, both hot air roasting and microwave processing treatments were evaluated. Hot air treatments were performed at temperatures of 50, 75, and 100°C from 15, 30, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 52 publications
2
39
0
Order By: Relevance
“…The effect of PEF treatment in peanut protein has also been explored recently. FT‐IR spectra showed significant alteration in protein structure (α‐helixes, β‐sheets, β‐turns, and random coils) as an effect of PEF treatment (Vanga et al., ). Thus, in general, PEF can also induce alterations in the structure and immunogenicity of food allergens.…”
Section: Effects Of Processing On Peanut Allergens and Immunogenicitymentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of PEF treatment in peanut protein has also been explored recently. FT‐IR spectra showed significant alteration in protein structure (α‐helixes, β‐sheets, β‐turns, and random coils) as an effect of PEF treatment (Vanga et al., ). Thus, in general, PEF can also induce alterations in the structure and immunogenicity of food allergens.…”
Section: Effects Of Processing On Peanut Allergens and Immunogenicitymentioning
confidence: 99%
“…Besides the major/potent peanut allergens, research indicates that some other minor allergens can also potentially cause life-threatening symptoms, while other allergens may only cause oral symptoms (Arkwright, Summers, Riley, Alsediq, & Pumphrey, 2013;Mittag et al, 2004;Petersen et al, 2014). Specific features of these proteins such as structure, digestibility, solubility, resistance to heat and digestion, and other functional properties such as glycosylation and enzymatic activity impart immunological sensitization and are the basis for the varying IgE reactivity, thus, allergenicity (Besler, 2001;Bøgh & Madsen, 2016;Huby, Dearman, & Kimber, 2000;Platts-Mills & Woodfolk, 2011;Vanga et al, 2016;Vanga et al, 2017). The peanut allergenic individuals also possess an 86% risk of being sensitized toward other nut allergies due to cross-reactivity Maloney, Rudengren, Ahlstedt, Bock, & Sampson, 2008).…”
Section: Molecular Characteristics Of Peanut Allergensmentioning
confidence: 99%
See 1 more Smart Citation
“…ese processing methods may induce protein modification, altering its intrinsic allergenicity through protein aggregation via disulfides or other interchain covalent bonds; all structural changes at the protein level may induce a concomitant disappearance or appearance of new IgE-binding epitopes [10][11][12]. Several authors reported that the thermal treatment causes changes in the structure/conformation of proteins in different matrix [13][14][15], depending on the structural and chemical properties of the protein itself, the type of thermal processing and the operating conditions applied (temperature, pH, and time) [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of incidence for β ‐sheet secondary structure in the control of A. platensis biomass was 38.5% (the most abundant), followed by random coil and α ‐helix, which represented 23.1% and 15.4%, respectively. The percentages of β ‐sheet and α ‐helix were similar to peanut protein and to α ‐chymotrypsin, trypsin, ribonuclease A and alcohol dehydrogenase …”
Section: Resultsmentioning
confidence: 99%